Relative Importance of Human Resource Practices on Affective Commitment and Turnover Intention in South Korea and United States - Lee, Jaeyoon; Sohn, Young Woo; Kim, Minhee; Kwon, Seungwoo; Park, In-Jo (Frontiers in Psychology, 2018)
The main purpose of this study was to investigate the impact of perceived HR practices on affective commitment and turnover intention. This study explored which HR practices were relatively more important in predicting affective commitment and turnover intention. A total of 302 employees from the United States and 317 from South Korea completed the same questionnaires for assessing the aforementioned relationships. The results illustrated that among perceived HR practices, internal mobility had the most significant association with turnover intention in both the US and South Korea. While internal mobility was a stronger predictor of affective commitment for the US sample, training was the most important variable for predicting affective commitment in South Korea. The second purpose of the study was to examine whether individuals’ positive affect influences the relationship between perceived HR practices and affective commitment and turnover intention. In the US, positive affect moderated the relationship between perceived HR practices and affective commitment and turnover intention such that the relationships were stronger for individuals reporting high positive affect relative to those reporting low positive affect. However, these relationships were not significant in South Korea. We discuss the implications of these results, study limitations, and practical suggestions for future research.